Improvisation and Social Aesthetics - Born, Georgina; Lewis, Eric; Straw, Will (Improvisation, Community, and Social Practice, 2017)
Addressing a wide range of improvised art and music forms-from jazz and cinema to dance and literature-this volume's contributors locate improvisation as a key site of mediation between the social and the aesthetic. As a catalyst for social experiment and political practice, improvisation aids in the creation, contestation, and codification of social realities and identities. Among other topics, the contributors discuss the social aesthetics of the Association for the Advancement of Creative Musicians, the Feminist Improvising Group, and contemporary Malian music, as well as the virtual sociality of interactive computer music, the significance of "uncreative" improvisation, responses to French New Wave cinema, and the work of figures ranging from bell hooks and Billy Strayhorn to Kenneth Goldsmith.